O trabalho da criança e do adolescente em face dos direitos humanos e do princípio fundamental da dignidade da pessoa humana - Freitas, Carla Rezende de (2018)
This current dissertation proposes a reflection about child’s and adolescent’s labor in Brazil, due to understand a theme that cannot be forgotten or disregarded by society, still being an unhappy reality that reproduces itself nowadays; although it has already significantly advanced, it still needs to go through a long way of civilization and consciousness, being indispensable to a major comprehension of the human rights and of the true meaning of the constitutional principle of the human dignity. Inevitably, child labor not only tortures the present generations, but also jeopardize the integrity of the upcoming generations, since today’s minor’s worker is the father who will accept tomorrow the premature inauguration of the labor’s life of his children, that for its part will repeat with the next generations the same twisted beliefs’ chain, thus creating generations and generations of men that did not have childhood, study, education and all the conditions that would obscure a life in its major potential. Categorically, it can be affirmed that minor workers will build a poorer society, less solidary, less free, on the opposite way of the search of an ideal society and civilization, being indispensable to recognize that the first step towards significant advances on the protection and formation of child and adolescent is the recognition of its hazard among society. Thus, to understand how significant is the child and adolescent labor is necessary to deeply study the human rights and the constitutional principle of the human dignity as a foundation of the fundamental human rights. It is required to highlight that one of the most detrimental ways of the human rights violation is the minor’s labor exploration, given that it excludes the child of his/hers school’s capacitation, healthy development and citizen’s conception. Therefore, unavoidably the child’s and adolescent’s protection nowadays constitutes in a regular preoccupation target, mostly in a globalized world that has a tendency of deterioration of the labor. It is not intended by this master’s dissertation to ignore the benefits of the adolescent inclusion in the labor world, reducing the minor labor discussion to an analyses done by a blind spot, however, what is intended here is to balance some peculiarities of the adolescent labor between the eradication and the regulation of it, analyzing the integration concept of the adolescent labor in the health and education dynamic among other aspects, always regarding the point of view of the human rights and the constitutional principle of the human dignity. In such context, this current master’s dissertation attempts to critically analyze the cruel reality that diminishes the human dignity which is the child labor, even when so many times its devastating consequences are ignored. There are countless marks that penetrates the body and soul of the children and the adolescents that have, in a premature way, their futures and hopes aborted by the survival instinct, the lack of possibilities, by ignorance, and by the lack of hope, being crucial to admit this hazard among the society, establishing dialogs, producing debates, shedding information, spreading reflections and proposing resolutions.